Assessment of genetic variability and molecular characterization of heat stress tolerant genes in Arachis hypogaea L. through qRT-PCR. (July 2019) - Kokkanti, Rekha Rani; Hindu, Vemuri; Latha, P.; Vasanthi, R.P.; Sudhakar, P.; Usha, Rayalacheruvu
Abstract: Temperature is the one of the most important environmental factor influencing plant growth and development limiting the crop productivity. Groundnut ( Arachis hypogaea L.) is a major crop cultivated in tropical and sub-tropical regions where high temperature stress is a serious constraint for its production. In the present study, groundnut genotypes were screened for thermotolerance using temperature induction response (TIR) technique, where the seedlings were exposed to sub lethal temperature from 38°C-54 °C for 5 h followed by lethal temperature at 58 °C for 3 h. From the 100 diverse genotypes screened, 24 genotypes showed tolerance to high temperature with mean percent seedling survival of 92%, 30 genotypes showed moderate tolerance and 46 genotypes were identified as temperature susceptible compared with checks (100% survival). The expression patterns of selected six groundnut genotypes Kadiri 9, Narayani, Dharani, JL 24, TPT-3 and Kadiri 6 at seedling stage were analyzed under heat stress using Quantitative real-time reverse transcriptase PCR (qRT-PCR). qRT-PCR analysis revealed stress responsive nature of the selected genes. Stress responsive genes such as heat shock protein 90 ( HSP90 ), dehydration responsive element binding-2A ( DREB2A ) and late embryogenesis abundant4-2 ( LEA4-2 ) showed more than 20–50 fold increase in expression level in selected genotypes. Highlights: Heat stress is one of the major abiotic stress factors that limit crop productivity worldwide. Using Temperature Induction Response technique, large populations can be screened within a short period of time. Highly tolerant and susceptible groundnut genotypes were identified using TIR technique. The expression analysis for selected induced groundnut seedlings for heat shock proteins and transcription factors revealed differential responses to heat stress.